Economic Development and the Church in French Canada - Ryan, S.J., William (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1966)
The author has chosen to dwell at some length of the methodology, limitations and general conclusions of his research project — his doctoral thesis presented at Harvard University. Among the more interesting findings of this research is the following : there appears to be little hard evidence that the Catholic Church exercised a significantly negative influence on the economic spurt that took place in Québec in the period 1896-1914.